Why are individuals with autism spectrum disorder at risk group for unhealthy weight? - Trambacz-Oleszak, Sylwia (Anthropological Review, 2019)
Several studies have indicated that the prevalence of unhealthy body weight in individuals with autism spectrum disorder (ASD) is high. It is unclear whether factors related to the weight status of children and adolescents with ASD are the same or different from factors associated with the weight status of typically developing children (TDC). The objective of this review was to identify key factors associated with the higher rates of unhealthy weight observed in individuals with ASD and create a structural model, which could be used for future autism intervention research. This review summarizes the current state of knowledge on the genetic basis of obesity in ASD, special treatment (behavioral and medical, including diet and psychotropic medications), psychological (depression and anxiety) as well as somatic comorbid disorders such as feeding problems, sensory processing disorders, gastrointestinal problems and sleep disorders, physical activity and sedentary behaviors, loneliness and social isolation, and family functioning (maternal depression and stress).